Disregarding the Reproductive Rights of Women in Child Marriage in Indonesia - Huzaimah, Arne; Abdillah, Muhammad; Laila, Nur Quma; Tamudin, M.; Puji Astuti, Tri Marhaeni (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
The phenomenon of child marriage frequently disregards children's reproductive rights. This study aims to explain the negligence of reproductive rights in child marriages by examining practices, factors, and the impacts of such neglect on girls' human rights. This paper employs a qualitative descriptive approach, and the data was gathered through the use of keywords to search the term